RETRACTED: Psychological and pedagogical technologies for the students’ sustainable behavior development - Dolgova Valentina; Kondratyeva Olga; Kapitanets Elena; Potapov Andrey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001